2012
DOI: 10.5337/2012.213
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater availability and use in Sub-Saharan Africa: a review of 15 countries.

Abstract: CITATIOn: Pavelic, P.; giordano, M.; Keraita, b.; Ramesh, V; Rao, T. (Eds.). 2012. groundwater availability and use in Sub-Saharan Africa: A review of 15 countries. Colombo, Sri Lanka: International Water Management Institute (IWMI). 274 p. KEyWORdS:groundwater development / groundwater potential / groundwater recharge / aquifers / groundwater irrigation / irrigated farming / groundwater policy / groundwater extraction / water availability / water storage / water quality / water use / domestic consumption / li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
77
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(77 citation statements)
references
References 8 publications
0
77
0
Order By: Relevance
“…The factors which occasion the massive failures in the water systems vary spatially and temporally. In South Africa, for instance, Pavelic et al (2012), Marks et al (2013) and, Eva (2015 attributed the mass failures in the water systems to inadequate technology and skills as well as to the shrinking service providers' budgets. A study undertaken in 2006 revealed that an additional 1,100 municipal plumbers were needed countrywide in order to cope with operation and maintenance of water service infrastructure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The factors which occasion the massive failures in the water systems vary spatially and temporally. In South Africa, for instance, Pavelic et al (2012), Marks et al (2013) and, Eva (2015 attributed the mass failures in the water systems to inadequate technology and skills as well as to the shrinking service providers' budgets. A study undertaken in 2006 revealed that an additional 1,100 municipal plumbers were needed countrywide in order to cope with operation and maintenance of water service infrastructure.…”
Section: Discussionmentioning
confidence: 99%
“…The big rivers including the Nile (4,000 miles), Niger (2,300 miles), Zambezi (1,899 miles), Congo (3,000 miles), Benue, Senegal, Orange, Limpopo, etc., are perennial and dynamic river resources (Jasper, 1976). Similarly; the Sahel region (Mali, Niger, Chad, and Burkina Faso) has abundant groundwater reserves (Pavelic et al, 2012). Majority of the residents in the region have entrenched dependence on wells and boreholes for the provision of water supplies (Gbadegesin & Olorundemi, 2007;Abaje et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However non-drought years can scarcely replenish the water deficit because too little of the meager rain that falls is retained long enough to help drive the processes supporting ecosystems and society. During the brief rainy season (4 months on average), precipitation occurs with very high variability in space and time and with such intensity that runs off often exceeds percolation, and groundwater levels are not replenished (Filippi et al 1990;Wang et al 2010;Pavelic et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Information on Kenya's groundwater resources is limited because extensive groundwater survey has not been done [20]. Furthermore, despite Kenya sharing an estimated 54% of its water resources with neighbouring countries, the state of the water resources within the shared basins and the probable future demands by neighbour countries has not been established, neither has operational trans- which outlines the strategy with which its mandate will be achieved [3].…”
Section: Water Sector Management In Kenyamentioning
confidence: 99%